디자인에서의 고급 감성 표현에 관한 연구 - 성소라(Sung, So RA); 나건(Nah, Ken) (한국디자인리서치, 2019)
본 연구는 비약적 경제성장을 통해 전세계가 주목하는 중국의 밀레니얼 세대와 그 부모세대의 감성언어를 중심으로 그들이 디자인에서의 고급 감성을 어떻게 표현하고 있는지 알아보기 위한 목적으로 진행되었다. 첫째, 문헌 고찰을 통해 세대 개념을 이해하고, 중국의 밀레니얼 세대와 부모세대의 특징을 정리하였다. 둘째, 시대변화에 따른 고급의 의미 변화에 대한 이해를 바탕으로 중국이 인식하는 고급에 대해 시대 문화적 배경을 바탕으로 정리하였다. 셋째, 앞선 문헌 연구를 바탕으로 북경에 거주하는 밀레니얼 세대와 부모세대를 대상으로 사용자 연구를 진행하고, 각 세대별 인식하는 디자인에서의 고급감성에 대해 분석하였다. 그 결과 밀레니얼 세대와 부모세대가 인식하는 고급감성은 사회문화적 배경에 따른 개인의 경험의 폭에 따라 상이한 것으로 나타났다. 감성은 개개인 마다 다르게 느끼는 것으로 객관화 된 결과 도출을 위해서는 더 많은 대상자를 대상으로 상황과 맥락을 고려한 후속 연구가 필요하다. This study focuses on the emotional language of the Millennials and their parents in China whose remarkable economic growth captures the attention of the entire world, aiming to see how they express their high emotional quality in their design. First, the study grasps the concept of generation and summarizes the characteristics of the Millennials and their parents in China through literature review. Second, based on its examination of the meaning of high emotional quality which changes with the times, the study has described the Chinese perception of high emotional quality based on the cultural background of the times. Third, based on previous literature studies, the study researches users, mainly the Millennials and their parents who live in Beijing, analyzed the high emotional qual in design as perceived by different generations. As a result, it has turned out that the high emotional quality as perceived by the Millennials and their parents differ with the width of personal experience as influenced by the sociocultural background. Sensibility is differently perceived by different people. So, getting at objective results requires follow-up studies which deal with more subjects and conduct research that focus on situation and context. KCI Citation Count: 0